'A lonely old man': empirical investigations of older men and loneliness, and the ramifications for policy and practice. Issue 4 (14th April 2021) - Ratcliffe, John; Wigfield, Andrea; Alden, Sarah
Abstract: Loneliness has become an issue of significant academic, public and policy focus. There has been much research on experiences of loneliness in later life and many accompanying interventions targeting lonely older people. However, there has been a dearth of research on the impact that loneliness can have on older men and the resulting implications for policy and practice. This paper aims to redress this by developing a theoretical framework to improve understanding of older men's constructions and experiences of loneliness. It draws on two qualitative empirical studies: the first explores older men's perceptions of masculinity and loneliness; and the second looks at the effectiveness of a service for older men which was designed to alleviate loneliness among older people more generally. The paper outlines the way in which older men often construct masculinity as an oppressive (hegemonic) requirement, but which can be reformed into 'positive' traits of 'strength of mind', 'responsibility', 'caring', 'helping out', 'doing a favour' and 'giving something back', with a consistent yet implicit assumption that enactment of these denotes a 'proud' masculine identity. Loneliness, on the other hand, is represented as a subordinate social role, both non-masculine and related to marginalising stereotypes of age. This results in the identification of two important implications for the way in which services can assist in the alleviation of loneliness in older men: that men are more likely to engage with a service that can facilitate the construction of a 'proud' masculine identity; and that services which deconstruct hegemonic masculinities, particularly by providing a space where men feel comfortable being emotionally tactile, are likely to be most effective at both alleviating loneliness and promoting overall wellbeing.